Do managers at two hierarchical levels differ in how they assess their company's market orientation? - Mateja Bodlaj (Journal for East European Management Studies, 2012)
The purpose of the presented empirical study was to examine the cultural and behavioural adoption of a market orientation as perceived by two groups of managers: general managers and marketing managers. With regard to marketoriented behaviours, a distinction is made between a responsive and a proactive market orientation. Based on a single-informant approach, comparisons between both groups of managers are made by testing invariant latent mean structures. An analysis of 363 companies from a South-east European country reveals that the general managers perceived all components of a market orientation significantly better than the marketing managers. – – Der Zweck dieser empirischen Studie ist es, die kulturelle und verhaltensmäßige Aneignung einer Marktorientierung durch zwei Gruppen von Managern (Geschäftsführer und Marketing-Manager) zu untersuchen. Im Hinblick auf marktorientierte Verhaltensweisen unterscheidet man zwischen einer reaktiven und einer proaktiven Marktorientierung. Basierend auf einem Ein-Informanten- Ansatz, wurden Vergleiche angestellt zwischen beiden Gruppen von Managern durch das Testen invariant latenter Mittelwert-Strukturen. Eine Analyse von 363 Unternehmen aus einem südosteuropäischen Land zeigt, dass die Geschäftsführer alle Komponenten einer Orientierung am Markt signifikant besser wahrnehmen als die Marketing-Manager.
Keywords: 650; market-oriented culture; market information; responsive and proactive market orientation